2021
DOI: 10.51893/2021.2.pov1
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of acute kidney injury: time to learn from implementations

Abstract: Acute kidney injury (AKI) is a major clinical problem in the community and in hospital, with hospital-acquired AKI reported in about 20% of adult and 30% of paediatric admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…First, few centres currently have access to rapid turn‐around biomarker assays to incorporate these into AKI diagnosis. However, this is now needed to allow clinicians to learn how to use kidney biomarkers in practice 100 . The second is that few kidney damage biomarkers have well characterized cut‐offs for diagnosis and such cut‐offs vary among different AKI contexts including clinical settings and comorbidities.…”
Section: Some Things Last Forever – the Consequences Of Akimentioning
confidence: 99%
See 1 more Smart Citation
“…First, few centres currently have access to rapid turn‐around biomarker assays to incorporate these into AKI diagnosis. However, this is now needed to allow clinicians to learn how to use kidney biomarkers in practice 100 . The second is that few kidney damage biomarkers have well characterized cut‐offs for diagnosis and such cut‐offs vary among different AKI contexts including clinical settings and comorbidities.…”
Section: Some Things Last Forever – the Consequences Of Akimentioning
confidence: 99%
“…However, this is now needed to allow clinicians to learn how to use kidney biomarkers in practice. 100 The second is that few kidney damage biomarkers have well characterized cut‐offs for diagnosis and such cut‐offs vary among different AKI contexts including clinical settings and comorbidities. Kidney biomarker thresholds that have been assessed in international studies are shown in Table 2 , but further studies are necessary to validate cut‐off values in specific populations.…”
Section: Some Things Last Forever – the Consequences Of Akimentioning
confidence: 99%
“… 4 Finally, the point of view article introduces and updates the concept of acute kidney injury (AKI) biomarkers and their meaning and utility. 5 All three are fundamental reading for Australian and New Zealand intensivists.…”
mentioning
confidence: 99%